2010
DOI: 10.1517/14656560903456053
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of oral cobalamin (vitamin B12) therapy

Abstract: Our experience and the present analysis support the use of oral cobalamin therapy in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
79
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 78 publications
(86 citation statements)
references
References 24 publications
0
79
0
3
Order By: Relevance
“…When FCM was identified as a major cause of cobalamin deficiency, the usefulness of oral supplementation in managing cobalamin deficiencies, which had previously been treated only by the parental route, was questioned and confirmed [28,29]. It should be noted from a practical point of view that only 1% of crystallin vitamin B12 (free) orally administered is absorbed by a passive diffusion mechanism (independently of intrinsic factor and cubilin) [7,28].…”
Section: Treatmentmentioning
confidence: 99%
See 4 more Smart Citations
“…When FCM was identified as a major cause of cobalamin deficiency, the usefulness of oral supplementation in managing cobalamin deficiencies, which had previously been treated only by the parental route, was questioned and confirmed [28,29]. It should be noted from a practical point of view that only 1% of crystallin vitamin B12 (free) orally administered is absorbed by a passive diffusion mechanism (independently of intrinsic factor and cubilin) [7,28].…”
Section: Treatmentmentioning
confidence: 99%
“…Since 1995, numerous clinical trials confirmed the non-inferiority of the oral route as compared to the parental route in the treatment of FCM, as evidenced by a normalisation of haematological abnormalities and regression of clinical symptoms, particularly neuropsychiatric manifestations, in the majority of patients [28,29]. It's important to keep in mind that early intervention is important to prevent permanent neurological damage.…”
Section: Treatmentmentioning
confidence: 99%
See 3 more Smart Citations